1998
DOI: 10.1161/01.cir.98.11.1048
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of Combined Percutaneous Transluminal Angioplasty and Minimally Invasive Direct Coronary Artery Bypass in Patients With Multivessel Coronary Artery Disease

Abstract: Background-Angioplasty has become an accepted treatment of patients with coronary artery disease and is now commonly used to treat patients with multivessel disease. The major disadvantage of angioplasty has been restenosis requiring repeat interventions with resultant loss of initial cost savings. Compared with the right and the circumflex coronary arteries, the left anterior descending artery (LAD) has been more adversely affected by restenosis. Recently, minimally invasive direct coronary artery bypass (MID… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0
1

Year Published

1999
1999
2012
2012

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(23 citation statements)
references
References 12 publications
1
21
0
1
Order By: Relevance
“…At least in small early-experience studies with short-term follow-up, hybrid revascularization appears feasible and safe. [41][42][43] However, an increased need for early antiplatelet therapy with the risk for bleeding complications and repeat revascularization, driven by IR and in-stent restenosis, may reduce the overall benefit. 8,44 In addition, Lichtenberg et al 45 showed that multivessel disease was an independent risk factor for adverse outcome in patients undergoing minimally invasive revascularization of the LAD using the internal thoracic artery (n=149), with, however, acceptable midterm morbidity and mortality.…”
Section: Implications: Is Reasonable Irmentioning
confidence: 99%
“…At least in small early-experience studies with short-term follow-up, hybrid revascularization appears feasible and safe. [41][42][43] However, an increased need for early antiplatelet therapy with the risk for bleeding complications and repeat revascularization, driven by IR and in-stent restenosis, may reduce the overall benefit. 8,44 In addition, Lichtenberg et al 45 showed that multivessel disease was an independent risk factor for adverse outcome in patients undergoing minimally invasive revascularization of the LAD using the internal thoracic artery (n=149), with, however, acceptable midterm morbidity and mortality.…”
Section: Implications: Is Reasonable Irmentioning
confidence: 99%
“…A recent report of 31 cases treated by combined LITA to LAD and PTCA showed the procedure to be safe and effective at least 7 months postoperatively. 6 In the present case, several conditions existed that were unfavorable to both conventional CABG and coronary stenting. Primary concerns were the patient's advanced age and hemorrahagic colon cancer.…”
Section: Discussionmentioning
confidence: 70%
“…A combination of PCI and CABG to treat multivessel coronary artery disease has been reported previously [8, 9, 11]. The present pilot study sought to assess the safety and feasibility of a same-day implementation of this approach in the treatment of severe two- or three-vessel coronary artery disease.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the right coronary artery (RCA) is an independent predictor of early saphenous vein aortocoronary bypass occlusion [7]. A ‘hybrid’ procedure combining surgical revascularization of multivessel coronary artery disease with IMA bypass and an additional percutaneous interventional procedure is considered to be an attractive treatment option in some patients [8, 9]. The aim of the present prospective study was to evaluate the feasibility, safety and efficacy of such a hybrid procedure combining initial RCA angioplasty and surgical left coronary artery revascularization using the left and/or right IMA in the following 16 h.…”
Section: Introductionmentioning
confidence: 99%